1974
DOI: 10.1073/pnas.71.6.2357
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Inactivation of Ovalbumin Messenger Ribonucleic Acid after Acute Withdrawal of Estrogen

Abstract: Synthesis of ovalbumin mRNA is induced and maintained in the avian oviduct by estrogen. When estrogen is rapidly removed from circulation, there is a general involution of the oviduct and an unusually rapid decay of ovalbumin mRNA activity. The kinetics of ovalbumin mRNA decay were not first order; instead, the rate of degradation increased about 10-fold over a 20-hr period after removal of estrogen. These results are in contrast with first-order decay kinetics observed for ovalbumin mRNA in estrogen-stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(52 citation statements)
references
References 20 publications
4
48
0
Order By: Relevance
“…In most steroid-regulated genes, gene expression is mainly influenced by changing the transcription rate (45), but significant differences in the stability of mRNA such as that of ovalbumin mRNA in the presence of estrogen (46), have been reported. In the present study, the RT-PCR assay demonstrated using the primers specific for ATla-R or ATlb-R gene, that the ATla-R mRNA level is increased by 2.1-fold in the presence of dexamethasone, whereas the AT 1 b-R mRNA level is unchanged by dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…In most steroid-regulated genes, gene expression is mainly influenced by changing the transcription rate (45), but significant differences in the stability of mRNA such as that of ovalbumin mRNA in the presence of estrogen (46), have been reported. In the present study, the RT-PCR assay demonstrated using the primers specific for ATla-R or ATlb-R gene, that the ATla-R mRNA level is increased by 2.1-fold in the presence of dexamethasone, whereas the AT 1 b-R mRNA level is unchanged by dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…We recognize that there may be stability features in endogenous mRNAs not present in exogenous reporter mRNAs, which are never as stable as long-lived endogenous mRNAs such as globin (Russell and Liebhaber 1996), ovalbumin (Palmiter and Carey 1974), and casein (Guyette et al 1979). Furthermore, exogenous mRNAs do not go through classical nuclear processing events, although it has been demonstrated that nucleoporation delivers the majority of nucleic acids into the nucleus (Martinet et al 2003;Kurosawa et al 2012).…”
Section: Decay Of a Polyadenylated Reporter Mrna Is Modulated By 59 Amentioning
confidence: 99%
“…This observation is not unique, in that changes in specific mRNA half-life with induction, hormonal changes, or cellular differentiation have been demonstrated in several system (35)(36)(37). In our rat model, uremia seems to influence albumin synthesis by an increased degradation of albumin mRNA by an apparent stimulation of ribonuclease activity.…”
Section: Discussionmentioning
confidence: 72%